2018
DOI: 10.1101/374983
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide Marginal Epistatic Association Mapping in Case-Control Studies

Abstract: Epistasis, commonly defined as the interaction between genetic loci, is an important contributor to the genetic architecture underlying many complex traits and common diseases. Most existing epistatic mapping methods in genome-wide association studies explicitly search over all pairwise or higher-order interactions. However, due to the potentially large search space and the resulting multiple testing burden, these conventional approaches often suffer from heavy computational cost and low statistical power. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 131 publications
0
19
0
Order By: Relevance
“…When disease prevalence is very low (e.g., k = 1%), cases are assumed to come from "tail" of the distribution. In this scenario, statistical models are generally better powered [27]. As the prevalence k becomes greater, such that the liability threshold moves from the tails to the center of the distribution, it will become harder for a classifier to distinguish cases from This also results in lower power for variable selection.…”
Section: Simulations With Binary Phenotypesmentioning
confidence: 99%
“…When disease prevalence is very low (e.g., k = 1%), cases are assumed to come from "tail" of the distribution. In this scenario, statistical models are generally better powered [27]. As the prevalence k becomes greater, such that the liability threshold moves from the tails to the center of the distribution, it will become harder for a classifier to distinguish cases from This also results in lower power for variable selection.…”
Section: Simulations With Binary Phenotypesmentioning
confidence: 99%
“…There are a few important takeaways from this formulation of MAPIT-R. First, the term m l effectively represents the polygenic background of all variants except for those that have been annotated for the l-th region of interest. Second, and most importantly, the term g l is the main focus of the model and represents the marginal epistatic effect of the region R l [43,44]. It is important to note that each component of the model will change with every new region that is considered.…”
Section: Overview Of the Mapit-r Modelmentioning
confidence: 99%
“…In contrast, the pathways with significant marginal epistatic effects identified in both the African and Chinese subgroups are pathways related to the immune system and contain multiple HLA loci (e.g., HLA-DRA, HLA-DRB1, HLA-A, HLA-B ) ( Supplementary Tables 5 and 6). These results are unsurprising since it is well known that the MHC region holds significant clinical relevance in complex traits [44,103,104,120]; however, more recent work has also suggested that Han Chinese genomes may be particularly enriched for interactions involving HLA loci [121].…”
Section: Evidence Of Epistasis Within the Non-african Subgroupsmentioning
confidence: 99%
“…For all synthetic demonstrations and assessments, we consider a simulation design that is often used to explore the utility of statistical methods across different genetic architectures underlying complex phenotypic traits [18,19,61]. First, we assume that all of the observed genetic effects explain a fixed proportion of the total phenotypic variance.…”
Section: Simulation Studiesmentioning
confidence: 99%
“…For example, understanding how statistical epistasis between genes (i.e. the polynomial terms of the variables in the genotype matrix) influence the architecture of traits and variation in phenotypes is of great interest in genetics applications [12][13][14][15][16][17][18][19]. However, despite studies that have detected "pervasive epistasis" in many model organisms [20] and improved genomic selection (i.e.…”
Section: Introductionmentioning
confidence: 99%